Preventing More "Missing Girls": A Review of Policies to Tackle Son Preference. (29th July 2019) - Kumar, Sneha; Sinha, Nistha
Abstract: In parts of Asia, the South Caucasus, and the Balkans, son preference is strong enough to trigger significant levels of sex selection, resulting in the excess mortality of girls and skewing child sex ratios in favor of boys. Every year, an estimated 1.8 million girls go "missing" because of the widespread use of sex selective practices in these regions. The pervasive use of such practices is reflective of the striking inequities girls face immediately, and it also has possible negative implications for efforts to improve women's status in the long term. Recognizing this as a public policy concern, governments have employed direct measures such as banning the use of prenatal sex selection technology, and providing financial incentives to families that have girls. This study reviews cross-country experiences to take stock of the direct interventions used and finds no conclusive evidence that they are effective in reducing the higher mortality risk for girls. In fact, bans on the use of sex selection technology may inadvertently worsen the status of the very individuals they intend to protect, and financial incentives to families with girls offer only short-term benefits at most. Instead, what seems to work are policies that indirectly raise the value of daughters. The study also underscores the paucity of causal studies in this literature.